Pooled prevalence and determinants of informed choice of contraceptive methods among reproductive age women in Sub-Saharan Africa: A multilevel analysis - Tsega, Nuhamin Tesfa; Haile, Tsion Tadesse; Asratie, Melaku Hunie; Belay, Daniel Gashaneh; Endalew, Mastewal; Aragaw, Fantu Mamo; Tsega, Sintayehu Simie; Gashaw, Moges (Frontiers in Public Health, 2022)
Background: Informed choice of contraceptive methods is a central component to increase contraceptive uptake, prevalence and its continuation. Despite the commitments of the government to minimize unintended pregnancy, abortion, and unmet need for contraceptives, as per our search of the literature, there is no study on the pooled prevalence and determinants of informed choice of contraceptive methods in sub-Saharan Africa. Therefore, this study aimed to assess the pooled prevalence and determinants of informed choice of contraceptive methods among reproductive-aged women in sub-Saharan Africa. Methods: This study was based on the Demographic and Health Survey, which was a cross-sectional population-based household survey conducted in 32 Sub-Saharan African. A total weighted sample of 65,487 women aged 15–49 who are currently using selected modern contraceptive methods was included in the study. The data were cleaned, weighted, and analyzed using STATA Version 14 software. Multilevel logistic regression modeling was used to identify determinates of an informed choice of contraceptive methods. Adjusted odds ratio (AOR) with 95% Confidence Interval (CI) and p value <0.05 were used to declare the significant determinants. Result: The pooled prevalence of informed choice of contraceptive methods among reproductive age (15-49) women in sub-Saharan Africa was 49.47% (95%CI: 44.33%, 54.62%) with I2 =99.5% and variations among countries were also observed ranges from 19.42% in Gabon to 78.42% in Senegal. Maternal aged 25-34 and 35-49 years, attending primary education, secondary education and higher education, having media exposure, using intrauterine device, injectable and implant, survey year 2016-2020, from lower middle and upper middle income level countries were associated with increased odds of informed choice of contraceptive methods. While accessing contraceptives from private clinics, pharmacies, and others, women in East Africa, Central Africa, and South Africa were associated with decreased odds of informed choice of contraceptive methods. Conclusion: Informed choice of contraceptive methods among reproductive age (15–49) women in sub-Saharan Africa was a major public health problem. Enhancing maternal education and media exposure, providing greater concern for the source of contraceptive methods, and strengthening the economic status of the country are recommended to enhance informed choice of contraceptive methods.